THE ANTECEDENTS OF VALUE RELEVANCE: A SYSTEMATIC LITERATURE REVIEW - Sasanti, Elin; Suartana, I Wayan; Wirama, Dewa Gede; Wirajaya, I Gde Ary (JRAK, 2024)
Research on value relevance in accounting reveals how market perceptions of accounting information are formed. Despite significant attention, a comprehensive explanation for variations in value relevance remains elusive. This study reviews the determinants of value relevance to identify gaps in the literature. Using PRISMA criteria, 47 empirical articles from 2013 to 2023 were examined across various countries. Findings indicate that International Financial Reporting Standards (IFRS) adoption and corporate governance significantly influence the value relevance of accounting information. While IFRS generally enhances financial statement comparability, outcomes vary in developing countries with weaker regulatory systems. Key factors also include board size, CEO duality, board diversity, macroeconomic conditions, and non-financial disclosures. The study employs agency and signaling theories to analyze these determinants, highlighting the complex factors affecting the utility of financial information for investors and calling for further research in underexplored contexts and on non-financial disclosures.